A nano-sized NbC precipitation strengthened FeCoCrNi high entropy alloy with superior hydrogen embrittlement resistance. (November 2022) - Chen, Heng; Ma, Yanan; Li, Chao; Zhao, Qiyue; Huang, Yunhua; Luo, Hong; Ma, Hongchi; Li, Xiaogang
Abstract: An equiatomic FeCoCrNi high entropy alloy (HEA) with high strength and excellent hydrogen embrittlement (HE) resistance is manufactured by the precipitation of nano-sized NbC during thermo-mechanical processing. NbC precipitates make the HEA obtain extraordinary mechanical properties via pinning dislocations. With the precipitation strengthening also comes the grain refinement strengthening. Furthermore, the coherent/semi-coherent NbC interfaces are regarded as reversible hydrogen traps based on thermal desorption analysis, thereby increasing the tolerance of HEA to dissolved hydrogen. Despite owning higher strength than the unreinforced one, the precipitation strengthened HEA still manifests superior HE resistance due to NbC preventing hydrogen transport by dislocations. Highlights: Nano-sized NbC dispersed in matrix via TMP can strengthen the HEA effectively. H bonding strengths are in the order of grain boundary> interstitial site> NbC. NbC prevents hydrogen transport by mobile dislocations to grain boundary. NbC strengthened HEA has lower HE susceptibility than the unreinforced one.